2020
DOI: 10.1186/s11671-020-03310-3
|View full text |Cite
|
Sign up to set email alerts
|

Metasurface Color Filters Using Aluminum and Lithium Niobate Configurations

Abstract: Two designs of metasurface color filters (MCFs) using aluminum and lithium niobate (LN) configurations are proposed and numerically studied. They are denoted as tunable aluminum metasurface (TAM) and tunable LN metasurface (TLNM), respectively. The configurations of MCFs are composed of suspended metasurfaces above aluminum mirror layers to form a Fabry-Perot (F-P) resonator. The resonances of TAM and TLNM are red-shifted with tuning ranges of 100 nm and 111 nm, respectively, by changing the gap between the bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 64 publications
(22 citation statements)
references
References 46 publications
0
22
0
Order By: Relevance
“…[79] The same research group also demonstrated two designs of high-efficiency reconfigurable color filter based on suspended rectangular Al and elliptical lithium niobate (LiNbO 3 ) metasurfaces on Si substrate coated with an Al mirror layer atop as shown in Figure 4(b). [80] Zhang et al proposed multilayer gratings by using superimposed metamaterial/metal/dielectric thin-films for hyperbolic spatial frequency filtering. This design performs the high extinction ratio of polarization characteristic in the visible light as shown in Figure 4(c) [81] .…”
Section: Reconfigurable Visible Metamaterialsmentioning
confidence: 99%
See 1 more Smart Citation
“…[79] The same research group also demonstrated two designs of high-efficiency reconfigurable color filter based on suspended rectangular Al and elliptical lithium niobate (LiNbO 3 ) metasurfaces on Si substrate coated with an Al mirror layer atop as shown in Figure 4(b). [80] Zhang et al proposed multilayer gratings by using superimposed metamaterial/metal/dielectric thin-films for hyperbolic spatial frequency filtering. This design performs the high extinction ratio of polarization characteristic in the visible light as shown in Figure 4(c) [81] .…”
Section: Reconfigurable Visible Metamaterialsmentioning
confidence: 99%
“…[84] In Figure 4(g), Tuan et al proposed a broadband metamaterial based on Figure 4. Reconfigurable visible metamaterials for (a) absorber, [79] (b) filter, [80] (c and d) polarizer, [81,82] (e) sensor, [83] (f) switch, [84] and (g) resonator [72] applications.…”
Section: Reconfigurable Visible Metamaterialsmentioning
confidence: 99%
“…On the basis of Pendry et al, the metamaterial based on SRR was fabricated by Smith et al [12], and they observed the negative refractive index phenomenon. Until now, many derivative structures have demonstrated-such as I-shaped SRR, U-shaped SRR, and 3D-SRR, and complementary structures [13][14][15][16][17][18]-which can be used to span the visible [19,20], infrared [21,22], and THz [23][24][25] spectra ranges. The electromagnetic characteristics of various metamaterials are Fano resonance [26], electromagnetically induced transparency effect [27], and spoof surface plasmons [28,29].…”
Section: Introductionmentioning
confidence: 99%
“…They are widely studied to realize thermal emitters and are perfect absorbers for energy harvesting, medical imaging, and high-sensitivity sensing applications [ 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 ]. By tailoring the geometrical dimensions, metamaterials can be designed to span broad operating wavelengths, including visible [ 31 , 32 , 33 ], IR [ 34 , 35 , 36 , 37 , 38 , 39 ], terahertz [ 40 , 41 , 42 , 43 , 44 ], and microwave light [ 45 , 46 ]. To provide metamaterials with more flexibility, there are many techniques proposed for tuning mechanisms using MEMS technology [ 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 ]: liquid crystal [ 55 ], photo-excited [ 56 ], phase-change materials [ 57 , 58 ], thermal annealing [ …”
Section: Introductionmentioning
confidence: 99%